A Pola Pengobatan dan Efek Samping Terapi Hormonal pada Pasien Kanker Payudara di RSUD Dr. Moewardi Surakarta - Niken Luthfiyanti; Vivin Marwiyati Rohmana; Muhammad Fuad Zidane Khusain (PHARMADEMICA : Jurnal Kefarmasian dan Gizi, 2026)
Breast cancer is one of the most prevalent malignancies in women and remains a leading cause of cancer-related mortality. One of the main treatment modalities for hormone receptor–positive breast cancer is Adjuvant Endocrine Therapy (AET), particularly tamoxifen, either as monotherapy or in combination. This study aimed to evaluate patient characteristics, treatment patterns of hormonal and chemotherapy regimens, as well as adverse drug reactions (ADRs) among breast cancer patients at Dr. Moewardi General Hospital, Surakarta. This study employed a cross-sectional design with purposive sampling. A total of 64 breast cancer patients who had received tamoxifen therapy for at least one month were included. Data were collected from medical records and questionnaires, and analyzed using the Chi-Square test to determine associations between variables. The results showed that most patients were <50 years old (60.9%) and diagnosed at advanced stages (III–IV, 57.8%). The most frequent treatment was a combination of chemotherapy and hormonal therapy (51.6%), while hormonal therapy alone was administered in 48.4% of patients. The most commonly prescribed chemotherapy regimen was Cyclophosphamide & Epirubicin, whereas the most frequent hormonal regimen was Tamoxifen + Zoladex. Bivariate analysis indicated significant associations between age and treatment type, as well as between cancer stage and treatment type (p<0,05). However, no significant associations were found between age, stage, or type of therapy and ADRs (p>0.05). The most commonly reported adverse effects were fatigue, hot flushes, nausea, and bone/joint pain, with a small proportion reporting endometrial cancer.